Lived experiences of refugee women with vaginal fistula in Nakivale and Oruchinga refugee settlements, Isingiro District, Uganda - George Opong; Everd Bikaitwoha Maniple; Caroline Noel Agabiirwe (BMC, 2024)
Abstract Background Vaginal fistula (VF) affects 2-3 million women globally, with the majority in Africa. In Uganda, it's 2%, with western Uganda having the highest prevalence. Major predisposing factors for refugee women include health system breakdowns and sexual violence during conflict. VF has severe consequences for women, relatives, and communities. There's limited information on lived experiences among refugee women with VF, and there's a need for quality prevention, treatment, and social reintegration strategies. This study aimed to understand the physical, psychosocial, and economic impacts of VF on refugee women in Nakivale and Oruchinga settlements and their coping mechanisms. Methods Ten refugee women with VF were interviewed using qualitative study design, utilizing Social-Ecological and Transactional Models for data collection, analysis, and discussion. Results Ten refugee women aged 24-50 years with or who had experienced VF participated in the study. They lived with VF for at least 2-15 years and had multiple stillbirths. Obstetric Fistula (OF) was the leading cause, followed by rape and cancer. Post-fistula, they faced social discrimination, emotional disturbances, survival difficulties, poverty, and lack of support. They struggled with stigma, social isolation, and marital sexual challenges. Conclusion Refugee women experience physical, emotional, financial, social, and sexual trauma due to VF. Discrimination and stigmatization from loved ones and society lead to isolation, depression, and suicidal thoughts. Despite successful repair, their social and emotional healing remains a burden for their lives. There is a need to provide a supportive environment for VF survivors.